Nieuwslijn: 'Mandela zegt: Premier Lubbers niet welkom in Zuid Afrika'. Statement of the ANC to the Heads of State not to visit South Africa until an Interim Government of National Unity has been installed
Nieuwslijn: 'Mandela zegt: Premier Lubbers niet welkom in Zuid Afrika'. Statement of the ANC to the Heads of State not to visit South Africa until an Interim Government of National Unity has been installed.